DAMPAK KEKERASAN BAHASA PENDIDIK TERHADAP PSIKOLOGIS PESERTA DIDIK - Lis Susilawati (IKIP Budi Utomo Malang, 2018)
It occurs frequently for many preceptorsconsider that this mien is the most effective one to control the protégé. Furthermore, it also aims to describe some factorsthat can trigger a verbal abuse, and then the last one is aimed to explain someverbal abuses that used by preceptor in teaching their protégé.This research figured out that the preceptor did seven kinds of verbalabuses, they are reprimanding the protégé, refusal, accusation, disparagement,judgment, forcefulness, and posing a threat. There are two causes of verbal abuse,they are the preceptor’s lack of knowledge about an appropriate teaching andstudent’s disobeying to the preceptors. Psychological effect of verbal abuse isdecreasing protégé’s psychology. The evidences is that the protégé take a bow andfeel fear when they see the preceptor.Based on these finding, it is recommended for preceptor not to do verbalabuse. Moreover, the headmaster should supervise the class activity successivelyto increase the quality of the preceptors.